Aberration Compensated Point Light Source Display With High-Resolution - Cao, Yulian; Chagnaadorj, Byamba-Ochir; Dalkhaa, Nomin-Erdene; Baasantseren, Ganbat (Frontiers in Photonics, 2022)
A high-resolution enhanced point light source integral imaging display is proposed. Using additional light sources to create extra point light sources in the point light source plane, the point light sources appeared on the plane that deviated from the expected values because of aberrations in the lens. Previously, only the lens array aberration was corrected and the distance along the horizontal and vertical axes was corrected too. The objective of this paper is to simultaneously correct the aberration between the lens array and the collimating lens, plus the horizontal and vertical axes, and correct the error along the z-axis. So, we determined the distance between the central light source and the additional light source to compensate for lens aberrations. From the experimental results, our technique precisely increased the resolution 3 times in both vertical and horizontal dimensions when compared to a traditional point light source display. Our method is applicable to 3D displays and compensates for the lens array and collimating lens aberrations.